Sifat Fisikokimia Pewarna Serbuk Antosianin Buah Murbei Hitam (Morus Nigra L.) Dengan Variasi Metode Pengeringan dan Bahan Pengisi - Anggun Dwi Amelia (Fakultas Teknologi Pertanian, 2025)
Black mulberry (Morus nigra L.) is a potential natural source of anthocyanins that can be used as a food colorant. This study aimed to determine the effect of drying methods namely thin-layer drying and spray drying, and filler concentrations, including maltodextrin and trehalose at 5% and 10%, on the physicochemical properties of black mulberry anthocyanin powder. Anthocyanin extract was obtained using the leaching or solid-liquid extraction method, followed by the application of different drying techniques. The analyzed parameters included yield, hygroscopicity, color, moisture content, anthocyanin content, percentage of anthocyanin loss, total polyphenol content, and antioxidant activity. The results showed that both drying method and type of filler had a significant effect on the physicochemical characteristics of the powder. Spray drying with 10% maltodextrin produced powder with higher yield, brighter color, higher lightness (L*) and chroma (C*) values, as well as better preserved antioxidant activity and anthocyanin content. In contrast, higher filler concentrations tended to reduce hygroscopicity. This study indicates that the combination of drying method and filler type plays an essential role in determining the quality of anthocyanin powder, supporting the development of natural colorants based on local fruits with improved stability and shelf life.
Reuploud repository Hasyim Juli 2026 Validasi dan Finalisasi Ratna 2 Juli 2026
Keywords: Black mulberry; anthocyanin; trehalose; maltodextrin.